L’espace public “revitalisé” comme gouvernance de l’intime - Emmanuelle Lenel (Ambiances)
This paper examines some effects of social regulation induced by regeneration policy. Based on the case study of a sports room designed in Brussels as part of a regeneration device, it highlights the role played by this kind of urban design in the relations to otherness within the public space. Using the concept of « forming » (Chelkoff), it particularly shows how some features of the building are made salient to the perception and thus influence the relationship to shared space and its users. Beyond the local case, it defends the general assumption that regeneration policy may contribute through urban design to the deployment or the narrowing of the intimacy sphere for social groups concerned and doing so, it influences the power relations at this level of experience.